Peran Guru dalam Mengatasi Perilaku Bullying pada Siswa Kelas IV SD Negeri XXV Wailiti Maumere - Vania Aurellia Barek Hoda; H. Amir Djonu; Nur Chotimah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to know the Role of Teachers in Addressing Bullying Behavior in Fourth Grade Students of XXV Wailiti Maumere Elementary School. The method used is a qualitative approach with data collection through interviews, observations, and documentation. The data sources in this study are primary and secondary data. The primary data obtained from the fourth-grade students and teachers of XXV Wailiti Maumere Elementary School, while the secondary data is collected from archives or school data and books and journals that support this research. Data analysis in this study was conducted before entering the field, during the fieldwork, and after completing the fieldwork. The activities in data analysis include data reduction, data presentation, and conclusion drawing. The research results show that the role of the teacher in addressing bullying behavior among fourth-grade students at XXV Wailiti Maumere Elementary School is that when there are problems, the class teacher calls the involved students, those who have issues are called one by one, the problems that occur are investigated, the issue is clarified first, the teacher identifies the problems that occur, the student who made the mistake is called and confronted, the student involved in the issue is asked one by one